2010
DOI: 10.1007/s12088-011-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Catalase and Superoxide Dismutase to the Intracellular Survival of Clinical Isolates of Staphylococcus aureus in Murine Macrophages

Abstract: The present study was performed in order to carefully investigate the interaction of Staphylococcus aureus with murine macrophages and the contribution of catalase and superoxide dismutase in intracellular persistence of Staphylococcus aureus within murine macrophages during in vitro infection. We have reported that Staphylococcus aureus internalized by murine macrophages did not appear to be rapidly killed. Data indicating the contribution of a single catalase and superoxide dismutase in intracellular surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…(catalyzing the conversion of H 2 O 2 to water and oxygen), while GST catalyzes a variety of reactions that detoxify endogenous compounds, including peroxidized lipids (Das and Bishayi 2010;Turkanoglu et al 2010). We found that both CAT activity and cat expression decreased with oxygen depletion.…”
Section: Discussionmentioning
confidence: 79%
“…(catalyzing the conversion of H 2 O 2 to water and oxygen), while GST catalyzes a variety of reactions that detoxify endogenous compounds, including peroxidized lipids (Das and Bishayi 2010;Turkanoglu et al 2010). We found that both CAT activity and cat expression decreased with oxygen depletion.…”
Section: Discussionmentioning
confidence: 79%
“…The adherent macrophages, more than 95% of which appeared to be typical macrophages by light microscopy, were used for each experiment. Murine peritoneal macrophages (5 × 10 6 cells/ml) were infected with S. aureus (5 × 10 6 CFU/ml) for 24, 48 and 72 h at 37 • C, in humidified 5% CO 2 incubator (Healforce, Model HF-151, China) in presence or absence of anti-TLR-2 antibody and after exogenous administration of MCP-1 the expression of TLR-2 or other proteins on macrophages were performed (Das and Bishayi, 2011).…”
Section: Isolation and Stimulation Of Peritoneal Macrophagesmentioning
confidence: 99%
“…Tumour necrosis factor ˛, interferon , interleukin-6, interleukin-1ˇ, interleukin 12p40, interleukin-10, MCP-1, MIP-1Ę LISA assays TLR-2 blocked murine peritoneal macrophages (5 × 10 6 cells/ml) were infected with S. aureus (5 × 10 6 CFU/ml) in a 1:1 cell: bacterium ratio (Das and Bishayi, 2011) in RPMI-FBS (5%) for 1 h to allow phagocytosis and then treated with rMCP-1 (100 ng/ml) and were further incubated for 24, 48 and 72 h at 37 • C cell culture incubator. After incubation cell culture supernatants were collected and stored at −70 • C prior to analysis.…”
Section: Assay For Determination Of Nitric Oxide (No)mentioning
confidence: 99%
“…Non-adherent cells were removed by aspiration and washing with RPMI 1640 medium before the addition of S. aureus. The adherent macrophages, more than 95 % of which appeared to be typical macrophages by light microscopy, were used for each experiment [38]. Murine peritoneal macrophages (5×10 6 cells/ml) were infected with S. aureus (5×10 6 CFU/ml) for 24, 48, and 72 h at 37°C in humidified 5 % CO 2 incubator (Heal Force, Model HF-151, China) in the presence or absence of anti-CXCR1 antibody; expression of CXCR1 on macrophages were performed.…”
Section: Isolation and Stimulation Of Peritoneal Macrophagesmentioning
confidence: 99%
“…Murine peritoneal macrophages (5×10 6 cells/ml) were mixed with S. aureus (5×10 6 CFU/ml) in a 1:1 cell/bacterium ratio [38] in RPMI-FBS (5 %) and incubated at 37°C cell culture incubator for different times in the presence and absence of anti-CXCR1 antibody (10 μg/ mL). After centrifugation, cell culture supernatants were collected and stored for further assay.…”
Section: Assays For Intracellular Killingmentioning
confidence: 99%